2022
DOI: 10.1155/2022/6041471
|View full text |Cite
|
Sign up to set email alerts
|

Associations among S100A4, Sphingosine-1-Phosphate, and Pulmonary Function in Patients with Chronic Obstructive Pulmonary Disease

Abstract: Background. S100A4 is a member of the S100 calcium-binding protein family and is increased in patients with chronic obstructive pulmonary disease (COPD). Sphingosine-1-phosphate (S1P) is a naturally occurring bioactive sphingolipid, which regulates the adhesion between the cells and the extracellular matrix and affects cell migration and differentiation. The goal of this study was to analyze the correlations among S100A4, S1P, and pulmonary function among COPD patients. Methods. All 139 serum samples and 15 lu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 50 publications
0
7
1
Order By: Relevance
“…causes lung fibrosis by promoting the proliferation and activation of fibroblast (42)(43)(44) and increased S100A4 elevation has been proposed to contribute in the development of IPF (45)(46)(47)(48). The S100A4 expression was significantly higher in intima layer across all arterial sizes however, we didn't find such a significant expression in media and adventitia layers.…”
Section: Discussioncontrasting
confidence: 66%
“…causes lung fibrosis by promoting the proliferation and activation of fibroblast (42)(43)(44) and increased S100A4 elevation has been proposed to contribute in the development of IPF (45)(46)(47)(48). The S100A4 expression was significantly higher in intima layer across all arterial sizes however, we didn't find such a significant expression in media and adventitia layers.…”
Section: Discussioncontrasting
confidence: 66%
“…IL-6 (JYM0140Hu) ELISA kits were obtained from Wuhan ColorfulGene Biological Technology Co ( http://www.jymbio.com/product/316-cn.html ). All ELISA procedures were carried out in accordance with our previous studies with minor adjustments [ 28 – 30 ].…”
Section: Methodsmentioning
confidence: 99%
“…S100A4 (also named fibroblast specific protein 1, FSP1) is considered a canonical mesenchymal marker in EMT with biological functions of promoting cell motility, invasion, ECM remodeling, autophagy, and angiogenesis [ 80 ]. Numerous studies have demonstrated that S100A4 was upregulated in COPD and inversely associated with airflow limitation [ 67 , 69 , 81 , 82 ]. Vimentin is expressed in all mesenchymal cells and is the core of EMT-mediated metastasis.…”
Section: Epithelial–mesenchymal Transformation In Chronic Obstructive...mentioning
confidence: 99%
“…The latest finding showed that serum S1P was upregulated and inversely associated with lung function in patients with COPD. In addition, serum S1P was positively associated with mesenchymal marker S100A4 in COPD [ 81 ]. Cullin 4A (CUL4A), an E3 ubiquitin ligase, is involved in the regulation of the cell cycle, DNA replication, and DNA damage repair [ 94 ].…”
Section: Epithelial–mesenchymal Transformation In Chronic Obstructive...mentioning
confidence: 99%